KONSTRUKSI IDENTITAS BUDAYA MELAYU RIAU MELALUI PROGRAM RONA MELAYU DI TVRI RIAU - Gusni Munika; Yasir ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Producer construction of Riau Malay cultural identity formed through commodities and communication with the main target being the Riau people in Riau Malay culture at LPP TVRI Riau. In forming Riau Malay cultural identity, producers use commodities associated with Riau Malay culture, such as dances, songs, culinary arts, and traditional clothing. Producers also use the right communication to reach the main target, namely the Riau people in Riau Malay culture. In this case, the producer pays attention to the language used, the values held by the people of Riau, as well as the traditions and habits that exist in the community. This study uses a qualitative method with a descriptive approach. There are ten informants taken through purvosive techniques. Types and sources of data were obtained through primary data and secondary data. Data collection was carried out by interviews, observation and documentation. Data analysis techniques by reducing data, presenting data and drawing conclusions. Furthermore, checking the validity of the data was carried out by extending participation and triangulation. The results of this study indicate that the producer's construction of Riau Malay cultural identity is formed through commodities and communication with the main target being the Riau people in Riau Malay culture at LPP TVRI RIAU. It can be concluded that mass media producers have a very important role in the formation of Malay cultural identity in Riau . Through the commodities they produce and the communications they make with the people of Riau, producers can form the desired Malay cultural identity. Mass media such as LPP TVRI Riau play an important role in shaping Malay cultural identity in Riau by presenting content based on Malay culture and exploring traditional values held by the people of Riau. Through these contents, producers can strengthen Malay cultural identity in Riau and introduce it to the wider community.